Influence of orocaecal transit time on hydrogen excretion after carbohydrate malabsorption. Issue 6 (June 1989) - Rumessen, J J; Hamberg, O; Gudmand-Høyer, E
Abstract : The aim of the present study was to determine whether changes in orocaecal transit time (OCTT) affect the magnitude of the breath hydrogen (H2) excretion after ingestion of unabsorbable carbohydrate. We studied eight healthy subjects by interval sampling of end expiratory H2 concentration for 12 hours after ingestion of: (1) 10 g lactulose (L); (2) 10 g L with 20 mg metoclopramide (M) as tablets; (3) 20 g L, and (4) 20 g L with 7.5 mg diphenoxylate (D) as tablets, in random order. In spite of significant changes in OCTT after M and D, there were no significant changes, compared for the same dose of lactulose, with respect to area under the breath H2 excretion curves, peak increments of H2 concentration or timing of the peak increment. We conclude that, within the ranges observed, the OCTT does not significantly affect the shape of the H2 concentration versus time curves. In comparative studies estimates of the degree of carbohydrate malabsorption on the basis of breath H2 concentration may be valid in spite of differences in OCTT.